BitS wins Islamic development bank transformers academy funding of RM1.08 Million - Universiti Putra Malaysia, Pejabat Strategi Korporat dan Komunikasi (2020)
SERDANG, Dec 18 – Given the current digital divide across the globe, a new shift in education approaches is needed to enhance the learning ecosystem